Le categorie aristoteliche nel prisma del diritto penale: Dialogo con Enrico Berti, per una teoria realistica del reato (Materiali di Estetica. Terza serie, 2022)
In September 2016, Enrico Berti gave an interview to the Paduan jurist Gabriele Civello on the relationship between Aristotelian philosophy and the general theory of Criminal Law. In particular, the interview concerns the connections between the Categories of Aristotle and the notion of Crime. The text is published here for the first time, in honor and memory of prof. Berti
Keywords: Categories; Aristotle; Crime; Criminal law